Identification of novel amino acid variants in the Han Chinese population that impair toll-like receptor 4 signaling and confer hyporesponsiveness to lipopolysaccharide - Zhou, Bin; Lv, Zhaoying; Zu, Ruijuan; Liu, Jianbo; Yang, Yuting; Zhou, Zongguang; Li, Yuan (Frontiers in Immunology, 2025)
IntroductionSevere acute pancreatitis (SAP), characterized by life-threatening inflammation and multiorgan failure, involves Toll-like receptor 4 (TLR4)-mediated hyperinflammation. This study investigates TLR4 variants’ impact on disease severity.MethodsSanger sequencing was performed in a Han Chinese cohort of patients with acute pancreatitis to screen for TLR4 variants. In silico analyses predicted structural consequences of identified missense variants on protein conformation, transmembrane domains, and isoelectric points. Co-immunoprecipitation assays assessed interactions between wild-type or mutant TLR4 and MyD88 in human embryonic kidney (HEK) 293T cells. Luciferase reporter assays and interleukin 8 (IL-8) expression tests evaluated nuclear factor kappa B (NF-κB) activation and downstream inflammatory signaling. To validate clinical relevance, knock-in mice carrying the Tlr4 p.(Arg804Trp) variant were generated, and SAP models were established to compare histopathological scores, apoptosis, immune cell infiltration, and serum biomarkers (amylase, lipase, IL-6, IL-10, tumor necrosis factor alpha) between homozygous mutant and wild-type controls.ResultsFive novel missense variants in TLR4 were identified in the Han Chinese cohort. In silico analyses predicted subtle alterations to the protein’s secondary structure for all five variants, with p.(Arg763Cys) specifically affecting the transmembrane domain and theoretical isoelectric point. Co-immunoprecipitation revealed that p.(Gly715Ser), p.(Arg763Cys), and p.(Arg804Trp) failed to interact with MyD88. Functional characterization in HEK293T cells confirmed that these three variants suppressed NF-κB activation and downstream IL-8 expression. In knock-in mice, homozygous Tlr4 p.(Arg804Trp) mutants exhibited significantly lower histological scores, reduced apoptosis, decreased neutrophil and macrophage infiltration, and lower serum levels of amylase, lipase, IL-6, and IL-10 compared to wild-type controls.CouclusionWe characterized novel TLR4 variants that compromise its signaling function, resulting in lipopolysaccharide hyporesponsiveness and attenuated SAP. These findings underscore the significance of genetic determinants in modulating SAP severity and advocate for TLR4-targeted interventions as a promising therapeutic approach.